Macrophage Transitions in Heart Valve Development and Myxomatous Valve Disease. Issue 3 (March 2018) - Hulin, Alexia; Anstine, Lindsey J.; Kim, Andrew J.; Potter, Sarah J.; DeFalco, Tony; Lincoln, Joy; Yutzey, Katherine E.
Abstract : Objective—: Hematopoietic-derived cells have been reported in heart valves but remain poorly characterized. Interestingly, recent studies reveal infiltration of leukocytes and increased macrophages in human myxomatous mitral valves. Nevertheless, timing and contribution of macrophages in normal valves and myxomatous valve disease are still unknown. The objective is to characterize leukocytes during postnatal heart valve maturation and identify macrophage subsets in myxomatous valve disease. Approach and Results—: Leukocytes are detected in heart valves after birth, and their numbers increase during postnatal valve development. Flow cytometry and immunostaining analysis indicate that almost all valve leukocytes are myeloid cells, consisting of at least 2 differentially localized macrophage subsets and dendritic cells. Beginning a week after birth, increased numbers of CCR2+ (C-C chemokine receptor type 2) macrophages are present, consistent with infiltrating populations of monocytes, and macrophages are localized in regions of biomechanical stress in the valve leaflets. Valve leukocytes maintain expression of CD (cluster of differentiation) 45 and do not contribute to significant numbers of endothelial or interstitial cells. Macrophage lineages were examined in aortic and mitral valves of Axin2 KO (knockout) mice that exhibit myxomatous features. Infiltrating CCR2+ monocytes and expansion of CD206-expressing macrophages are localized in regions where modified heavy chain hyaluronan is observed in myxomatous valve leaflets. Similar colocalization of modified hyaluronan and increased numbers of macrophages were observed in human myxomatous valve disease. Conclusions—: Our study demonstrates the heterogeneity of myeloid cells in heart valves and highlights an alteration of macrophage subpopulations, notably an increased presence of infiltrating CCR2+ monocytes and CD206+ macrophages, in myxomatous valve disease. Abstract : Supplemental Digital Content is available in the text.